TWO CASES WITH ANGILIPOMAS WHOSE MIMIC LEPATO CELLULAR CARCINOMA - Saadeddin HÜLAGÜ; Levent DEMİRTÜRK and Zeki ÇANKIR and Selami ALBAYRAK and Ethem KARAŞEN and Eşref KIZILKAYA and Yavuz ÖNAL and Mehmet ALTIN (Turkish Journal of Gastroenterology, 2020)
-